Cycling As an Element of Sustainable Urban Mobility: A Case Study of Poland - Joanna DROBIAZGIEWICZ (Communications of International Proceedings, 2023)
The introduction of solutions supporting the implementation of sustainable development policy is an important and topical issue. One of the important areas of this concept is sustainable mobility, which is considered both on an international, national and local scale. Sustainable urban mobility can be considered both in the context of environmental protection and the need to ensure efficient, economic and safe urban transport. Cycling transport, whose role has recently increased considerably, deserves attention. The aim of this paper is to fill the research gap by identifying key aspects of cycling for further research, assessing the current status of cycling and providing recommendations for improving cycling infrastructure in Poland. The paper is divided into two main sections. The first part of the research, based on a review of the literature and relevant documentation, highlights the importance of cycling and identifies means of promoting its growth. The following part is an empirical study that analyses statistical data obtained from a database of public institutions and international organisations. The studies conducted reveal a continuous enhancement in the state of cycling facilities in Poland, which includes the expansion of cycling routes. Urban areas experience particularly rapid growth in the development of this mode of transportation. The implementation of state-of-the-art IoT solutions also plays a crucial role. The concluding section of the article suggests implementing further measures to improve conditions for the continued development of urban cycling transport.
Keywords: smart city; cycling; sustainability; urban transport; sustainable mobility